2017
DOI: 10.1007/s00276-017-1908-x
|View full text |Cite
|
Sign up to set email alerts
|

Does formalin fixation influence MSCT/CBCT accuracy?

Abstract: Our results suggest that formalin fixation of an anatomical specimen does not substantially affect the accuracy of a three-dimensional image generated with CBCT and MSCT. Thus, fixed specimen can be used in future investigations of 3D models without concerns regarding the accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…With specimens embalmed in formalin for several years before this study, optical density might have decreased, irrespective of imaging modality [25]. While Seidel et al [26] found no substantial difference between the diagnostic accuracy of MDCT and CBCT scans of a cadaveric specimen with and without formalin fixation, particularly the long-term effects of such fixation are not fully understood. Moreover, despite the blinded evaluation of scans, readers might have become accustomed to the characteristic image traits of each scanner over the time of their reads.…”
Section: Discussionmentioning
confidence: 72%
“…With specimens embalmed in formalin for several years before this study, optical density might have decreased, irrespective of imaging modality [25]. While Seidel et al [26] found no substantial difference between the diagnostic accuracy of MDCT and CBCT scans of a cadaveric specimen with and without formalin fixation, particularly the long-term effects of such fixation are not fully understood. Moreover, despite the blinded evaluation of scans, readers might have become accustomed to the characteristic image traits of each scanner over the time of their reads.…”
Section: Discussionmentioning
confidence: 72%
“…The resolution of the 3D data captured or imported into the software plays a crucial role in precision and needs to depict the object under investigation as precisely as possible. The method used in this study has been analysed in previous research, and the spatial resolution of CBCT images and the generated 3D models fall within an acceptable clinical range of <300 μm (Dach et al, 2018; Seidel et al, 2017). As all models were created in the same manner, they were directly comparable.…”
Section: Discussionmentioning
confidence: 99%
“…The deviations within the ROI were evaluated both linearly and volumetrically (Figure 2d–j). The used evaluation technique is a highly precise method for evaluating 3D digital data while avoiding errors made, for example, by manual measurements (Dach et al, 2018; Seidel et al, 2018; von Wilmowsky et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The individual steps applied in this study were based on previous research that examined the accuracy of each step. The precision of the high-performance industrial optical scanner (Atos SO II, GOM GmbH) for digitising the impressions was 3 µm [ 34 ], and the accuracy of the converted 3D CBCT models was 400 (± 229) µm for 0.3 voxels [ 48 ]. The merging workflow was performed in a precise, two stage approach (manually and with a best-fit-algorithm), where images were registered by the tooth surfaces.…”
Section: Discussionmentioning
confidence: 99%